Evaluasi Perubahan Penggunaan Lahan Kecamatan di Daerah Aliran Sungai Cisadane Kabupaten Bogor - Trimarwanti, Tessie Krisnaningtyas Endang (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Bogor Regency is part of the National Strategic Area Jabodetabekpunjur, serves as the buffer area. There are two Nature Conservation Area and seven Watershed, the greatest area is Cisadane Watershed, rich biodiversity, daily needs, but susceptible of land use change, especially high population area. The purpose study is to find out land use change and its influence factors on sub-district located in Cisadane Watershed, Bogor Regency. This study used mixed methodes research with series/multiply research, the first is spatial approach and quantitative analysis and the second is qualitative approach. It had been occured before the provision of wetland agricultural area. Economic-social factors trigger developers the function of agricultural into housing with value added, no exception resident with the right ownership. Another factor is institutional factors, lack of commitment service from government to presence infrastructure and sustainability irrigation flow. The application of space utilization control has been conducted by sub-district and district officials through supervision and control accordance with the provisions of RTRW/IMB regulation, but this has offset by socialization to the public so a lot of society and officials government have yet know and understand the rules, so tendency land use change is quite high.